Analisis Kinerja Perusahaan Peraih Penghargaan Proper Emas Terhadap Green House Gas Emission Disclosure: Indonesia Case 2013-2020 - DESI WAHYUNI (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2021)
ABSTRACT- This research was conducted to test the company's performance based on the money metric and the ratio of greenhouse gas emission disclosures. The test was conducted on 31 companies that received a Proper gold ranking in 2013-2018 with multiple linear regression analysis. The results showed that simultaneously the company's performance based on money metrics and ratios had a positive effect on the disclosure of greenhouse gas emissions with a probability of 0.0031. However, after being partially tested only one variable has a significant effect but the effect is negative, the variable is sales. While the other five variables namely Ebitda, Profit, Asset, Price, and Roe did not show a significant effect. Therefore, the need for an education about the disclosure of greenhouse gas emissions that is different from the disclosure of corporate social responsibility. Keywords: disclosure, greenhouse gas emissions, company performance, proper